Effects of equivalence ratio on performance and emissions of diesel engine with hydrogen and water injection system at variable injection timing - Adnan, R.; Sabri Adlan, Z.; Munir, Fudhail Abdul; Mahlia, Teuku Meurah Indra; Masjuki, Haji Hassan (IJENS Publisher, 2018)
This paper aims to develop a comprehensive development and research for performance and emissions of diesel engine fueled with hydrogen and water at variable injection timing. Experiments have been conducted to compare the performance and emissions between diesel alone, diesel with hydrogen and hydrogen-diesel and water injection pressure. addition of hydrogen into diesel engine resulted in higher pressure which lead to huge indicated work. Furthermore, injecting water into diesel engine with hydrogen mixture indicated a desirable outcome. Existence of water in combustion slightly decreased the amount of emissions but opposite in term of performance. The fact is water injection exist in combustion will absorb a portion of heat release which will result low in combustion process thus lead to low in performance production otherwise production of NOx emission is low. In conclusion, humidification in combustion engine is a great idea toward a high performance and low in emissions production compared to diesel alone operation which leads to a green technology production.